The impact of organizational learning on Polish and Finnish SME’s market performance during the COVID-19 pandemic. A comparative study - Sikora Tomasz; Baranowska-Prokop Ewa (International Journal of Management and Economics)
This article focuses on the role of small and medium-sized enterprises’ (SMEs) organizational learning (OL), measured by a scale of commitment to learning, and their economic performance during the COVID-19 pandemic. The research is based on two samples of firms from Poland and Finland. Interviews with owners and managers of Polish and Finnish SMEs were conducted in December 2020 and January 2021. The results show that OL was quite high among the analyzed firms, with the exception of Polish non-exporters. Unlike the “pre-COVID-19” sample of Polish SMEs, the results of the two “COVID-19” samples showed no significant relationship between the applied measure of OL and firms’ market performance. The analyses indicate a significant impact of COVID-19-related disruptions on market performance measures for both Polish and Finnish enterprises. Thus, we conclude that firms’ turnover and profits have been affected by turbulences on particular markets and firms’ ability to benefit from various assistance programs offered by governments.